Children's stress during a restorative dental treatment: assessment using salivary cortisol measurements - (:unkn) unknown (My University, 1996)
Dental environment may be a source of stress for the young patient. Such stressful conditions may provoke fear in anxious children. It is well known that stress produces an activation adrenal steroid secretion. Among the methods for assessing child dental fear, measurement of salivary cortisol level is a simple method, because especially in children, sampling of saliva is easy, and cortisol levels in saliva closely mirror serum free cortisol levels, independent of salivary flow rate. For this study, the salivary cortisol levels of 8 children (mean age 5.6 yr) were measured receiving initial dental treatment. Saliva samples were collected via cotton rolls placed to the floor of the mouth at four stages; prior to treatment, during cavitation, placement of the liner and the restoration. Statistical comparison of the results were done by Student-t test. The increase in salivary cortisol levels during cavitation at the first and secondary appointments were significant (p<0.01 and p<0.05), but not at the second. The other comparisons were not statistically significant (p>0.05). The results of this study suggest that in restorative procedures, mostly it is the cavitation step that creates stress and anxiety in children. Knowledge of the most stressful condition may be helpful for the dentist to prepare the child to treatment steps.
Keywords: Female; Humans; Male; Child; Child, Preschool; Saliva; Stress, Psychological; Dental Cavity Preparation; Dental Restoration, Permanent; Dental Anxiety; Dental Care for Children; Hydrocortisone